Cultural Resources and Developing Community Tourism in Vietnam - Trang, Nguyen Thi Thu (Journal of Posthumanism, 2025)
The development of each country relies on many resources, including cultural resources - the spiritual foundation of society, both diverse and tangible, intangible; cultural products are expressed in the form of material products, spiritual products. Vietnam has a long history of development with cultural diversity of residential communities - diverse indigenous cultures; and many cultural heritages - scenic spots, historical relics, becoming a great advantage in cultural resources to implement development goals, including the goal of developing community tourism. On that basis, many localities in Vietnam have developed community tourism, making an important contribution to economic growth and implementing social development management goals. This study addresses cultural resources in two contents, including cultural heritage, indigenous culture; and assesses the impact of cultural resources on community tourism development. The theoretical framework is built with a 3-scale model in the direction of assessing the practical development of community tourism and the impact of cultural heritage and indigenous culture on community tourism development. The author conducted a survey of 570 leaders of local authorities at the commune level and leaders of cultural and tourism organizations in 3 provinces of Vietnam - localities with advantages in cultural heritage and indigenous culture to develop community tourism, including Son La province (North), Quang Nam province (Central), Ben Tre province (South). From the results of the above empirical research, the author draws scientific conclusions and discusses policy issues that can be applied to Son La, Quang Nam province, Ben Tre province and many localities in Vietnam.